Investigation of novel superparamagnetic Ni0.5Zn0.5Fe2O4@albumen nanoparticles for controlled delivery of anticancer drug. (8th August 2017) - Qasim, Mohd; Asghar, Khushnuma; Dharmapuri, Gangappa; Das, D
Abstract: In the present work, multifunctional Ni0.5 Zn0.5 Fe2 O4 @albumen (NZF@Alb) and doxorubicin-loaded Ni0.5 Zn0.5 Fe2 O4 @albumen (NZF@Alb-Dox) core–shell nanoparticles have been prepared by a green and simple method using inexpensive chicken egg albumen and have been characterized for different physiochemical properties. The structural, morphological, thermal, and magnetic properties of the prepared nanoparticles have been investigated by an x-ray diffractometer, high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy, Fourier-transformed infrared, thermogravimetric analysis, and vibrating sample magnetometer techniques. Superparamagnetic Ni0.5 Zn0.5 Fe2 O4 nanoparticles (NZF NPs) with the mean size ∼20 nm were coated with albumen matrix by an ultrasonication process. Inverse fast Fourier transform-assisted HRTEM micrographs and FTIR analysis revealed the coating of amorphous albumen on crystalline NZF NPs. NZF@Alb and NZF@Alb-Dox NPs have the mean size (D50 ) of ∼100 nm, good stability, and magnetic controllability. Magnetic measurements (field (H)-dependent magnetization (M)) show all samples to be super-paramagnetic in nature. Biocompatibilities of the NZF and NZF@Alb NPs were confirmed by in vitro 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay against RAW 264.7 cells. NZF@Alb NPs have been found to be more biocompatible than bare NZF. In Vitro Dox release behavior from NZF@Alb-Dox NPs has been studied at pH 7.4 and 5, and a sustained and pH-dependent drug release profile were observed. In vitro cytotoxicity or anticancer activity of the blank NZF@Alb NPs, free Dox, and NZF@Alb-Dox NPs against HeLa cells (cancer cell line) were also examined by MTT assay. The obtained results suggest that this scalable egg-albumen-based magnetic nanoformulation is suitable for targeted drug delivery applications. Thus, the present study could be extremely useful for the advancement of albumin-based nanocarrier design and development for biomedical applications such as targeted and controlled delivery of anticancer drugs.